(untitled) (Modern American Journal of Engineering, Technology, and Innovation, 2025)
During the research, 4 different samples with different compositions were produced on a single-needle 156-needle sock knitting machine of the Chinese company Kejun KJ6F606 model, and their physical and mechanical properties were studied.